Strong Diffusion of Energetic Electrons by Equatorial Chorus Waves in the Midnight‐to‐Dawn Sector. Issue 22 (23rd November 2019) - Kasahara, S.; Miyoshi, Y.; Kurita, S.; Yokota, S.; Keika, K.; Hori, T.; Kasahara, Y.; Matsuda, S.; Kumamoto, A.; Matsuoka, A.; Seki, K.; Shinohara, I.
Abstract: Drastic variations of radiation‐belt/ring current electrons are the result of competing processes of acceleration, transport, and loss. For subrelativistic energetic electrons (10–100 keV), one of the promising loss mechanisms is precipitation into the atmosphere due to pitch angle scattering by whistler mode chorus waves. The efficiency of the scattering has yet to be quantified by direct observations, however. Using in situ measurements by the ERG (Arase) spacecraft in the midnight‐to‐dawn sector at and around the magnetic equator, we demonstrate that the full filling of energetic electron loss cones occurs commonly, associated with typical‐amplitude (greater than 50 pT) chorus waves. The spatial distribution of the loss cone filling indicates that the efficient scattering is limited to |MLAT|< 10°. Plain Language Summary: Drastic variations of high‐energy (10–100 keV) electrons in the Earth's magnetosphere are the result of competing processes of acceleration, transport, and loss. In order to understand their dynamics, therefore, it is important to quantify each process. One of the promising loss mechanisms is precipitation into the atmosphere due to the interaction with electromagnetic waves called "chorus waves." However, the precipitation rate has yet to be quantified by direct observations in the interaction region. Using in situ measurements by the ERG (Arase) spacecraft in the magnetosphere, we demonstrate that the full throttle precipitation occurs commonly, associated with typical‐amplitude (greater than 50 pT) chorus waves. The observed spatial distribution indicates that the efficient interaction is confined at/around the magnetic equator. Key Points: Spatial distribution of medium‐energy loss cone electrons in the low‐latitude magnetosphere is shown for the first time The strong diffusion is common when chorus waves are active Strong scattering occurs only at the near‐equatorial region (|magnetic latitude|< 10°) in the midnight‐to‐dawn sector